Serpentine - Hamilton, Laurell K. (Anita Blake, vampire hunter novels, 2018)
"Return to vampire hunter Anita Blake's thrilling world in the next novel by the New York Times bestselling author of Crimson Death. Anita Blake faces new, even deadlier enemies as she and the people she loves confront major changes in their lives, in the latest thrilling adventure featuring the fan favorite vampire hunter"--